2022
DOI: 10.1029/2022gl098513
|View full text |Cite
|
Sign up to set email alerts
|

Marsh Sedimentation Controls Delta Top Morphology, Slope, and Mass Balance

Abstract: River deltas and their marsh platforms host diverse ecosystems threatened by anthropogenic impacts to coastal areas, such as rising sea levels, subsidence, and leveeing of channels (Ericson et al., 2006). Organic material production, a critical form of sediment accumulation in many river deltas, is the primary driver of marsh platform growth (Nyman et al., 2006), whereas clastic sedimentation via rivers drives deltaic lobe growth (Edmonds et al., 2009). To successfully predict the long-term fate of these ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…These deltas are constructed by flows that have a higher sediment to water ratio than field-scale systems, resulting in higher delta slopes and significantly altered morphodynamics (Sanks et al, 2023). Delta topset slopes tend to be multiple orders of magnitude lower than those observed in the control experiment, with similar slopes only widespread on the subaqueous foreset (Edmonds et al, 2011;Sanks et al, 2022a). While creep has been observed in coastal environments, we know of no field data that shows such tight elevation-control of subsidence rates.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These deltas are constructed by flows that have a higher sediment to water ratio than field-scale systems, resulting in higher delta slopes and significantly altered morphodynamics (Sanks et al, 2023). Delta topset slopes tend to be multiple orders of magnitude lower than those observed in the control experiment, with similar slopes only widespread on the subaqueous foreset (Edmonds et al, 2011;Sanks et al, 2022a). While creep has been observed in coastal environments, we know of no field data that shows such tight elevation-control of subsidence rates.…”
Section: Discussionmentioning
confidence: 96%
“…Each experiment was allowed to prograde for 120 hr before hour zero of run time. The treatment experiment differed only in that a proxy for marsh sedimentation was applied to regions near sea level (−9 to 5 mm relative to sea level, hereafter RSL), resulting in about 8% of the final deposit mass and 15% of the final deposit volume (Sanks et al., 2022a). Therefore, significant statistical differences in subsidence rates can be attributed to the impact of the marsh proxy deposits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not believe that all of these additional forcings would significantly change the results found here; Van De Lageweg and Slangen (2017) simulated delta evolution over centennial timescales with different forcing and SLR conditions, and found river, tidal, and wave‐dominated deltas all responded similarly to SLR. Conversely, studies examining the role of subsidence and faulting (e.g., A. J. Moodie & Passalacqua, 2021; Liang, Kim, & Passalacqua, 2016), vegetation and marsh growth (e.g., Lauzon & Murray, 2018; Sanks et al., 2022), and ice and permafrost (e.g., Lauzon et al., 2019; Piliouras et al., 2021) have shown that these processes can influence delta morphology and channel mobility. Therefore, future studies should endeavor to explore a different parameter space, using results from this work to limit the SLR scenarios considered, and aim to understand how additional processes or coupled changes to forcings, such as rising sea levels and a flashier input hydrograph, may alter deltaic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies examining the role of subsidence and faulting (e.g., A. J. Liang, Kim, & Passalacqua, 2016), vegetation and marsh growth (e.g., Lauzon & Murray, 2018;Sanks et al, 2022), and ice and permafrost (e.g., Lauzon et al, 2019;Piliouras et al, 2021) have shown that these processes can influence delta morphology and channel mobility. Therefore, future studies should endeavor to explore a different parameter space, using results from this work to limit the SLR scenarios considered, and aim to understand how additional processes or coupled changes to forcings, such as rising sea levels and a flashier input hydrograph, may alter deltaic evolution.…”
Section: Study Limitations and Opportunities For Future Workmentioning
confidence: 99%